Pengaruh Promosi Kesehatan pada Media Jingle terhadap Pengetahuan dan Praktik Cuci Tangan Pakai Sabun pada Siswa SD Negeri 147 Kota Palembang - Selfana Wahda, Azza; Sukarjo, Sukarjo; Kamsul, Kamsul; Intan Kumalasari; Khairil Anwar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Handwashing with soap is essential to eliminate germs and prevent disease transmission. In 2024, Palembang City recorded 34,350 cases of diarrhoea, with the highest at Gandus Health Centre 2,729 cases. This study aims to examine the effect of health promotion using jingle media on the knowledge and practice of handwashing with soap among students of SD Negeri 147 Palembang. This research employed a quantitative approach with a pre-experimental design, specifically a one-group pre-test–post-test. The population consisted of all Year V students, with a sample of 60 students selected through total sampling. Data were collected using questionnaires and observation sheets. The study revealed an increase in the average knowledge score from 23.33 (pre-test) to 92.50 (post-test), and in practice from 28.54 to 89.58. The Wilcoxon test showed a p-value of 0.000 for both variables. The findings indicate that jingle media significantly improved knowledge (mean difference = 65.17; p = 0.000) and handwashing practice (mean difference = 61.04; p = 0.000). Schools are encouraged to continue supporting and facilitating handwashing education through engaging media, such as jingles, to enhance clean and healthy behaviour among students.